Religiosity in Health Related Lifestyle Behaviour: Study of Muslims in Malaysia - Hassan, Siti Hasnah (2012)
Consumers are increasingly sensitive to factors affecting their health. Billions of dollars have been spent on health related activities by the government, non-government organizations and private agencies that involved preventive health measures. In recent years, the concepts and issues of spirituality and religiosity have been given more attention by scholars, policy makers, and profit and non-profit organizations. This can be seen in certain evidence in respect of the rapid growth of many Islamic banks, the Halal industry, schools, and other institutions around the world, as well as in western countries. Recently, religion has become more prominent in shaping attitude, values and behaviour, as individuals experience a religious reawakening.